Fundamentos de la Escuela Austriaca sobre el capital y los ciclos económicos e invitación al diálogo con la síntesis neoclásica; Austrian Economics fundamentals on capital and economic cycles and invitation to dialogue with the neoclassical synthesis - Antonio Sánchez-Bayón; Marcos Castro-Oliva (Atlantic Review of Economics (ARoEc), 2023)
– Review of economic fundamentals and invitation to dialogue between economic schools for a better understanding and management of economic cycles. It is based on the theory of capital and the economic cycles of the Austrian Economics, since it is one of the few that considers money non - neutral and ir warns of the risks about the new money due to credit expansions without savings or expansive budgets without income. To explain the fundamentals and to promote dialogue with other schools, this review starts wit h Garrison model on the Macroeconomics of capital, analyzing its evolution, with greater depth and better systematization of extensions and applications, in tax matters, foreign trade, etc. This review aims to advance the reconciliation of economic theory and econometrics, but without excessive mathematization or mathiness, that is far from reality. In this way, a smoother transition is suggested from the neoclassical synthesis to the heterodox synthesis in the digital age.
Keywords: A12; B5; E3; E5; F4; 330; Austrian Economics; capital theory; economic & business cycle; economic crisis; capital-based Macroeconomics